Translasi dan Uji Validitas Isi Questionnaire on Satisfaction with Clinical Practice for Students - Irma Yusanti; Anastasia Anna; Ayu Prawesti Priambodo (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Student satisfaction is one of the main indicators in evaluating the effectiveness of clinical learning. Assessing nursing students' satisfaction with clinical learning is a crucial aspect in evaluating the quality of nursing education. However, to date, there is still limited availability of standardized, valid, and reliable instruments or questionnaires in Indonesian that specifically measure nursing students' satisfaction with clinical learning, particularly regarding clinical practice. To translate and validate the content of the Questionnaire on Satisfaction with Clinical Practice for Students (QSCP-S) into an Indonesian version to ensure that the questionnaire items retain their original conceptual meaning and are relevant to the Indonesian context. This process included forward translation, backward translation, expert review, and content validity testing. The translation process was carried out by six translators, and the content validity test was conducted by seven nursing experts. Data were analyzed using I-CVI, S-CVI/UA, S-CVI/Ave, and CVR to determine the relevance, clarity, and essentiality of the instrument. The recommended I-CVI and CVR values are 0.78. The scores for the 23 items in the Indonesian version of the QSCP-S questionnaire were: relevance (I-CVI) 0.86-1.00; S-CVI/Ave 0.98; S-CVI/UA 0.91; clarity (S-CVI/Ave 0.87); and essentiality (CVR 1.00). The Indonesian version of the QSCP-S questionnaire demonstrated good validity. The items were revised based on the expert's suggestions and recommendations, with the original questionnaire remaining at 23 items. Keywords: Clinical Practice, Content Validity Test, Student Satisfaction, Translation.  ABSTRAK Kepuasan mahasiswa merupakan salah satu indikator utama dalam mengevaluasi efektivitas pembelajaran klinik. Penilaian terhadap kepuasan mahasiswa keperawatan dalam pembelajaran klinik merupakan aspek krusial dalam evaluasi mutu pendidikan keperawatan. Namun, hingga saat ini, masih terdapat keterbatasan dalam ketersediaan instrumen atau kuisioner yang terstandarisasi, valid dan reliabel dalam bahasa Indonesia yang secara spesifik mengukur kepuasan mahasiswa keperawatan terhadap pembelajaran klinik khususnya tentang praktik klinik. Translasi dan validitas isi Questionnaire on Satisfaction with Clinical Practice for Students (QSCP-S) ke dalam versi bahasa Indonesia untuk menjamin butir-butir kuisioner mempertahankan makna konseptual aslinya dan relevan dengan konteks Indonesa. Proses ini mencakup tahapan forward translation, backward translation, expert review, dan uji validitas isi (content validity). Proses translasi dilakukan oleh 6 penerjemah dan uji validitas isi oleh 7 orang expert di bidang keperawatan. Data dianalisis dengan I-CVI, S-CVI/UA, S-CVI/Ave dan CVR untuk mengetahui relevansi, kejelasan dan essensialitas instrumen. Nilai I-CVI dan CVR yang direkomendasikan 0,78. Nilai dari 23 item pernyataan dalam kuisioner QSCP-S versi Bahasa Indonesia adalah relevansi I-CVI 0.86-1.00;S-CVI/Ave 0.98; S-CVI/UA 0.91, kejelasan S-CVI/Ave 0.87, esensialitas CVR 1.00. Kuisioner QSCP-S versi Bahasa Indonesia menunjukkan uji validitas kategori baik, item-item dalam kuisioner direvisi sesuai saran dan rekomendasi penilai (expert) dan dipertahankan berjumlah 23 item sama seperti kuisioner versi aslinya. Kata Kunci: Kepuasan Mahasiswa, Praktik Klinik, Translasi, Uji Validitas Isi.